Distribution. Known only from type locality in N Sumatra. in Muridae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Distribution. Known only from type locality in N Sumatra. Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 836, DOI: 10.5281/zenodo.6887260